Percaturan Politik Geneologi Kekuasaan Dalam Sistem Pemilu ‘2024’ Di Indonesia Perspektif Etika Michel Foucault - Yohanes Alfrid Aliano; Mathias Jebaru Adon (Jurnal Filsafat Indonesia, 2023)
The focus of this research is to examine more deeply the meaning of Michel Foucault's Politics of Power in the democratic system of the '2024' general election in Indonesia. The author places the electoral system in its universal realm, while the 2024 election serves as a trigger to analyze more deeply the political genealogy of power in Indonesia, which in recent years has needed to be discussed in political-philosophical discourse. The purpose of this study is to analyze the philosophical ethical values ​​of the democratic system in Indonesia, which are starting to receive special attention ahead of the 2024 elections. Foucault's power ethics refers to the role of Indonesian democracy which remains on the constitutional basis of democracy which is sovereign from the people, by the people and for the people. By using a qualitative method of Foucault's ethical philosophy, the authors discuss it in a contextual comparative study with the political situation in Indonesia. The author finds through genealogy analysis of power politics is a democracy that will never be separated from power politics in any government system. Thus, a policy of philosophical critical thinking is needed to question the origins, construction, and effects of existing power practices in elections so that everyone who plays the political arena remains based on constitutional foundations, namely Pancasila and the 1945 Constitution.